2001
DOI: 10.1007/s003470170164
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Befunde bei autosomal-rezessivem Syndrom der Blauzapfenhypersensitivität

Abstract: The enhanced S-cone sensitivity syndrome was expressed to a different degree of severity and probably inherited in an autosomal recessive mode. These unusual ERG findings may be due to a depressed rod system and an increased number of S-cone photoreceptors, postreceptoral circuits, and S-cone sensitive ganglion cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…All p.R311Q-patients presented with the symptoms consistently found in recessive NR2E3-linked retinal degenerations as described above. Clumped pigment deposits were shown to involve the macula in one 60-year-old patient, but not in his contemporary first cousin, in line with the previously observed high intrafamilial variability [Jurklies et al, 2001;Pachydaki et al, 2009]. These two patients had no cystoid maculopathy or macular schisis, whereas a 20-yearold patient suffered from cystoid maculopathy, subretinal hemorrhage, and subfoveal neovascularization [Nakamura et al, 2002].…”
Section: Genotype-phenotype Relationshipssupporting
confidence: 73%
See 2 more Smart Citations
“…All p.R311Q-patients presented with the symptoms consistently found in recessive NR2E3-linked retinal degenerations as described above. Clumped pigment deposits were shown to involve the macula in one 60-year-old patient, but not in his contemporary first cousin, in line with the previously observed high intrafamilial variability [Jurklies et al, 2001;Pachydaki et al, 2009]. These two patients had no cystoid maculopathy or macular schisis, whereas a 20-yearold patient suffered from cystoid maculopathy, subretinal hemorrhage, and subfoveal neovascularization [Nakamura et al, 2002].…”
Section: Genotype-phenotype Relationshipssupporting
confidence: 73%
“…These symptoms are also present in other retinal degenerations, e.g., congenital stationary night blindness (CSNB; MIM]s 163500, 257270, 300071, 310500, 610427, 610444, and 610445(, fundus albipunctatus (MIM] 136880), retinitis punctata albescens (MIM] 136880), and crystalline corneoretinal Bietti dystrophy (MIM] 210370). However, the ERGs from CSNB patients are different from those affected by ESCS [Jurklies et al, 2001]. In fundus albipunctatus, dark adaptation is markedly prolonged.…”
Section: Differential Diagnosismentioning
confidence: 88%
See 1 more Smart Citation
“…In a proband without NR2E3 mutation (Patient A), the following retinal function studies were specifically performed: static threshold perimetry in the dark-adapted (500-and 650-nm stimuli) and light-adapted (600-nm stimulus on 2.7 log td white background; 440-nm stimulus on a 4.0 log td yellow background) states using a modified automated perimeter, to determine the retinal sensitivities to light of different wavelengths (Humphrey Field Analyzer, San Leandro, CA); full-field electroretinography (ERG) to determine the electrical responses of the retina to light ; and cross-sectional retinal imaging with optical coherence tomography (OCT3, Zeiss Humphrey Instruments, Dublin, CA). The methods used to characterize phenotype were those used in our previous studies of ESCS-NR2E3 Roman and Jacobson, 1991;Kellner et al, 1993;Hood et al, 1995;Haider et al, 2000;Jurklies et al, 2001;Milam et al, 2002;Cideciyan et al, 2003). Informed consent for all procedures was obtained from subjects after the nature of the studies had been explained.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…It is characterized by night blindness, cystoid maculopathy and degenerative changes of the vascular arcades (Marmor 1989; Jacobson et al 1990, 1991; Marmor et al 1990; Roman & Jacobson 1991). Patients with ESCS have been reported worldwide, including in Japan (Kellner et al 1993; Yamamoto et al 1999; Jurklies et al 2001; Nakamura et al 2002). Full‐field and spectral electroretinographic findings have shown that while patients with ESCS have severely reduced responses of the rods, 30‐Hz flicker, and middle (M) and long wavelength‐sensitive (L) cones, they have hypersensitive responses of the S‐cones (Jacobson et al 1990; Marmor et al 1990; Hood et al 1995; Greenstein et al 1996).…”
Section: Introductionmentioning
confidence: 99%